Arabic and foreign sources describing the cultural heritage of the historic city of Fez - Alshamsi, Aisha; Chatra, Khireddine (Al-Adab Journal, 2024)
Fez, the ancient city over its history, attracted researchers, travelers, geographers, orientalists, and scholars of various. They were fascinated by its diverse architecture, such as the religious buildings like mosques, and the military architecture like walls, gates, towers, "Kasbat", and other buildings such as palaces, schools, hotels, markets, and many others.In addition, the city of Fez had a widespread scientific status, where Al Qarawiyyin Mosque played a major role in reinforcing the scientific movement in the Maghreb, as it is considered the oldest university in the world. We intend through this study to shed light on all that has been written about the cultural heritage of Fes, especially the ancient architectural heritage. Among what will be discussed is an extrapolation of all the Arab sources that provided detailed information about its original buildings, the most important architectural formations and the aesthetic elements that distinguish them. Then, we will monitor the foreign sources that describe this architectural heritage. In this research, we have relied on a large number of Arab and foreign references, the most important of which is »«Kitab Al Anis Al Muṭrib Birawḍ Al Qirṭas Fi Akhbar Muluk Al Maghrab Wa Tarikh Madinah Fas»« (The Entertaining Companion Book in the Gardens of Pages from the Chronicle of the Kings of the Maghreb and the History of the City of Fes) by Ibn Abi Zar'a, "Kitab Janai Zahret Al A'as Fe Benaa Madinah Fas" (the Book of Reaping the Flower of Myrtle in Building the City of Fes), by Al Jaznai, "Kitab Wasf Ifreqiya" (the Description of Africa Book), by Hassan Al Wazzan, known as the African Lion, and "Fas Qabl Al Himaya" (Fes Before the Protection), by Roger Lauterno, and other references.Based on the information contained in those references, and through the historical and descriptive approaches, the research found that some references mentioned the same architectural landmarks in general, but with different details, such as the city gates, their names, and the period in which they were built. The study hypothesized - relying on a number of reliable primary references - that the city of Fes abounds with a cultural (intangible-architecture) heritage rooted in history, and that the city of Fes historically enjoyed a widespread scientific status.The study, primarily, relied on archival historical references that dealt with this topic and with some aspects of that era and the events that followed it. In addition, it did not overlook contemporary sources, as well as what was mentioned in the subsequent references from information and statistics on relevant aspects. These references contributed to introducing researchers to the cultural heritage owned by the city of Fes, to understand the historical development that occurred in this heritage, and to conduct comparative studies on what was left by the successive states that ruled them. In addition, they described their periods of prosperity, vigor, and periods of decline and retreat, by paying attention to the reconstruction of the city, with its various urban functions.